Distribuição de cladóceros planctônicos (Crustacea: Branchiopoda) em um reservatório eutrófico raso (Paraná, Brasil) - Ghidini, André Ricardo; Serafim-Júnior, Moacyr; Perbiche-Neves, Gilmar [UNESP]; de Brito, Lineu (My University, 2009)
This study focused the spatial and temporal distribution of the composition, abundance, and diversity of planktonic cladocerans from eutrophic, Iraí Reservoir, as well as their relationships with some biotic and abiotic variables. The tested hypothesis was that cladocerans present higher variation in a temporal than in a spatial scale. The samples were taken monthly in 6 stations, from March/02 to July/03. Twenty-four taxa were identified, distributed in 7 families, the richest families being Daphniidae (6 spp.), Chydoridae (6 spp.), and Bosminidae (5 spp.). The most frequent and abundant species were Bosmina hagmanni, Moina minuta, and Ceriodaphnia cornuta. The highest abundances were found in September/2002. Temporally, rainfall influenced organism's distribution, while spatially cladocerans were more affected by reservoir hydrodynamics and wind action. The low species richness could be a reflection of the trophic state of the reservoir, in which a dominance of Cyanobacteria was observed during that study period. Both scales showed high variation, but only the temporal scale showed significant difference to richness and abundance. Nearby the end of this study, higher stable values of species richness were recorded, which could suggest an increase in the water quality due to des-pollutions actions.
Distribution of planktonic cladocerans (Crustacea: Branchiopoda) of a shallow eutrophic reservoir (Paraná State, Brazil)
Keywords: Cladocera; Cyanobacteria; Eutrophication; Iguaçu river basin; Iraí reservoir; Bosmina hagmanni; Bosminidae; Branchiopoda; Ceriodaphnia cornuta; Chydoridae; Crustacea; Daphniidae; Moina minuta